(untitled) (Journal of Partial Differential Equations, 2025)
In this paper we will study the existence of one, two and three weak solutions for a class of variable exponent elliptic equations under appropriate growth conditions on the nonlinearity. Our technical approach is based on the existence theorems obtained by G. Bonanno.